2015
DOI: 10.1111/irv.12306
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of preventive behaviors in response to the 2009 H1N1 influenza pandemic: a multiethnic perspective

Abstract: BackgroundAs public health leaders prepare for possible future influenza pandemics, the rapid spread of 2009 H1N1 influenza highlights the need to focus on measures the public can adopt to help slow disease transmission. Such measures may relate to hygiene (e.g., hand washing), social distancing (e.g., avoiding places where many people gather), and pharmaceutical interventions (e.g., vaccination). Given the disproportionate impact of public health emergencies on minority communities in the United States, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 27 publications
5
54
5
1
Order By: Relevance
“…Self-e cacy [27,53], trust [27,30,52], attitude or advantages [53,67], and gender [27,64,67,68] have all been reported previously as determinants of avoidance or social distancing behaviour. In other studies, aspects of risk perception [23,24,51,61], perceived effectiveness of avoidance behaviours [28,30,52,69] and ethnicity [28,65] have been shown as determinants for this behaviour, in contrast to this study. While for perceived effectiveness of measures, the difference may have been due to wording of question as a knowledge question, as described for hand hygiene behaviours, it is not known why risk perception and ethnicity were not signi cant in this study.…”
Section: Determinants Of Social Distancing Behaviourcontrasting
confidence: 99%
See 2 more Smart Citations
“…Self-e cacy [27,53], trust [27,30,52], attitude or advantages [53,67], and gender [27,64,67,68] have all been reported previously as determinants of avoidance or social distancing behaviour. In other studies, aspects of risk perception [23,24,51,61], perceived effectiveness of avoidance behaviours [28,30,52,69] and ethnicity [28,65] have been shown as determinants for this behaviour, in contrast to this study. While for perceived effectiveness of measures, the difference may have been due to wording of question as a knowledge question, as described for hand hygiene behaviours, it is not known why risk perception and ethnicity were not signi cant in this study.…”
Section: Determinants Of Social Distancing Behaviourcontrasting
confidence: 99%
“…Participants with higher risk perception, as identi ed in a broader sense by other university student surveys in previous pandemics [21][22][23], or the general population in the COVID-19 pandemic [52,61,62], were also more likely to perform hygiene behaviours in the current study. Those of non-white ethnicities were also found to have greater likelihood of carrying out hygiene behaviours in this study, as was found in general population surveys in other studies or previous pandemics [28,[63][64][65].…”
Section: Determinants Of Hand Hygiene Behavioursupporting
confidence: 87%
See 1 more Smart Citation
“…5 A previous study in the US revealed variations between ethnic groups in adoption of preventive behaviors of influenza. 6 To assess medical college students' KAP toward influenza in a low-income multiethnic setting we conducted this study.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear, why CCCDs who identified as racial minorities were more willing to implement OHPPs within the next year, compared to Whites. The literature shows contradictory findings regarding racial/ethnic minorities adopting preventive behaviors compared to Whites [ 15 17 ]. Evidence shows that child care staffs with a formal college education or above provide more sensitive and appropriate care to children with asthma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%